APARECEN SOMBRAS CRIMINALES: ARTE Y POLÍTICA EN LA POESÍA DE CARMEN BERENGUER. - Leal, Francisco (Revista de Critica Literaria Latinoamericana, 2007)
The article discusses the relationship between poetry and politics. The author proposes the hypothesis that, for poetry and politics to be understood together, they must be stripped of specifics. He explores this hypothesis through works by Chilean poet Carmen Berenguer. For poetry and politics to coincide, there must be a certain gap in the relevancy of one to the other, and for this to occur, there must be a complex distance between the two, the author states. He asserts that Berenguer's words sometimes complement the political and economic consensus and sometimes do not. He claims that value is generated when poetry conflicts with politics.